2022
DOI: 10.3390/antib11030059
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Possible Factors Influencing the Neutralizing Anti-SARS-CoV-2 Antibody Titer after Six Months from the Second Vaccination Dose in a Sample of Italian Nursing Home Personnel

Abstract: The titer of the anti-SARS-CoV-2 antibodies produced after vaccination shows a relevant decay over time, as demonstrated in several studies. However, less is known on the possible factors affecting the entity of this decay. The aim of this study is to analyze a group of individual factors which are possibly associated with anti-SARS-CoV-2 antibody titer decay six months after the second vaccine dose. We report here the results of a follow-up serological analysis and a questionnaire-based evaluation of a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 29 publications
4
10
0
Order By: Relevance
“…This cohort study conducted among HCWs and residents of 13 LTCFs in Northern Italy found IgG titers 2 weeks after a full vaccination cycle were significantly upregulated compared with before vaccination among all participants. Our results add to an emerging literature supporting the real‐life effectiveness of mRNA vaccines in inducing detectable antibody responses in this setting 2,13,16–19 …”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This cohort study conducted among HCWs and residents of 13 LTCFs in Northern Italy found IgG titers 2 weeks after a full vaccination cycle were significantly upregulated compared with before vaccination among all participants. Our results add to an emerging literature supporting the real‐life effectiveness of mRNA vaccines in inducing detectable antibody responses in this setting 2,13,16–19 …”
Section: Discussionsupporting
confidence: 68%
“…Our results add to an emerging literature supporting the real‐life effectiveness of mRNA vaccines in inducing detectable antibody responses in this setting. 2 , 13 , 16 , 17 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Facility staff were also included in the priority group for vaccination [13][14][15][16]. Nursing home staff can be a source of transmission for residents and may also be exposed to contagion when attending to residents´physical care needs.…”
Section: Introductionmentioning
confidence: 99%